Pengaruh Perkembangan Teknologi terhadap Pendidikan Islam - Unik Hanifah Salsabila; Muhammad Lutfi Nur Hanifan; Muhammad Ibnu Mahmuda; Muhammad Afif Nur Tajuddin; Anggi Pratiwi (Departement of Mathematics Education, 2023)
Islamic Religious Education is a subject that has been given to students from an early age, with the intention of familiarizing children with the Religion of Islam. The introduction of Islamic religious education to children has developed in every era, from those who previously used books or lectures, to now using electronic learning media. Islamic religious education learning media has many kinds of media and models, such as visual, audio, and audio-visual media. The development of the all-digital era certainly has positive and negative impacts, the positive impact is that learning is more interesting and can adapt to the potential of students, and the negative impact is that it is easy to find information what children want, with the fear of finding something that leads to negative things.